(untitled) (Medical Forum Monthly, 2020)
Objective: To explore the perception of students regarding Team Based Learning (TBL) in Pathology at Rashid Latif Medical and Dental College, Lahore. Study Design: Descriptive cross-sectional study Place and Duration of Study: This study was conducted at the Rashid Latif Medical and Dental College, Lahore, in December 2019. Materials and Methods: A total of 151 students who were present at the time of survey in pathology third year MBBS class and expressed their consent for participation were enrolled in the study. A structured validated questionnaire was used as a study tool. Results: A total of 151 undergraduate medical students responded to the questionnaire. The perceptions regarding team based learning was very satisfactory. Majority of the student agreed that team based learning (TBL) is a better teaching methodology for learning pathology. Conclusion: Current teaching methods in medical colleges need to be improved. Team based Learning is a student centered learning. New teaching strategies should be implemented to engage student in learning.